2019
DOI: 10.1371/journal.pbio.3000535
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced translation expands the endo-lysosome size and promotes antigen presentation during phagocyte activation

Abstract: The mechanisms that govern organelle adaptation and remodelling remain poorly defined. The endo-lysosomal system degrades cargo from various routes, including endocytosis, phagocytosis, and autophagy. For phagocytes, endosomes and lysosomes (endo-lysosomes) are kingpin organelles because they are essential to kill pathogens and process and present antigens. During phagocyte activation, endo-lysosomes undergo a morphological transformation, going from a collection of dozens of globular structures to a tubular n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 115 publications
1
41
0
Order By: Relevance
“…As lysosomes are key in maintaining neural stem cell quiescence ( 106 ), a dysregulation and accumulation of storage material in the cell that requires increase lysosome biogenesis ( 107 , 108 ) as occurs in neuronal lipofuscinosis, could signal OPC senescence. Thus, this change reflect an adaptation of the lysosome to changes in the energy state of aged OPCs or to a higher inflammatory environment, similar to that shown in activated phagocytes, cancer cells and other inflammatory diseases ( 109 , 110 , 111 ). These increases in lysosomes and autophagy could also be a cell-intrinsic compensatory mechanism in response to ageing cues ( 77 ).…”
Section: Discussionmentioning
confidence: 54%
“…As lysosomes are key in maintaining neural stem cell quiescence ( 106 ), a dysregulation and accumulation of storage material in the cell that requires increase lysosome biogenesis ( 107 , 108 ) as occurs in neuronal lipofuscinosis, could signal OPC senescence. Thus, this change reflect an adaptation of the lysosome to changes in the energy state of aged OPCs or to a higher inflammatory environment, similar to that shown in activated phagocytes, cancer cells and other inflammatory diseases ( 109 , 110 , 111 ). These increases in lysosomes and autophagy could also be a cell-intrinsic compensatory mechanism in response to ageing cues ( 77 ).…”
Section: Discussionmentioning
confidence: 54%
“…Lrrk2 GS/GS cells did not show any intensification of neural red staining suggesting a possible impairment in their ability to ingest extracellular α-syn. In phagocytes, it was recently reported that the endo-lysosomal compartment undergoes adaptation, remodeling, and expansion during particle internalization through an enhanced translation [87]. In this regard, our findings might suggest that striatal astrocytes harboring the G2019S mutation in Lrrk2 also fail to adapt and expand their endo-lysosomal system when they are stimulated to phagocytize, resulting in α-syn-defective internalization.…”
Section: Discussionmentioning
confidence: 60%
“…This bolus of amino acids may be sensed by intraluminal amino acid sensors like the V-ATPase, or by cytoplasmic sensors like CASTOR, after amino acid transport across the phagolysosome membrane, locally promoting mTORC1 activation (Saxton et al, 2016; Chantranupong et al, 2016; Zoncu et al, 2011; Inpanathan and Botelho, 2019). While mTORC1 drives many anabolic processes like protein and lipid synthesis, mTORC1 also plays a role in coordinating phagosome and lysosome dynamics, including efferosome fission (Krajcovic et al, 2013; Inpanathan and Botelho, 2019; Saric et al, 2016; Hipolito et al, 2019). Thus, cargo degradation coupled to mTORC1 activation could help orchestrate phagosome resolution.…”
Section: Discussionmentioning
confidence: 99%
“…While mTORC1 drives many anabolic processes like protein and lipid synthesis, mTORC1 also plays a role in coordinating phagosome and lysosome dynamics, including efferosome fission (Krajcovic et al, 2013;Inpanathan and Botelho, 2019;Saric et al, 2016;Hipolito et al, 2019).…”
Section: Cargo Degradation In Phagolysosome Resolutionmentioning
confidence: 99%